Treatment of Osteochondral Fracture of the Lateral Femoral Condyle with TWINFIX Ti Suture Anchor “X”‐Shaped Internal Fixation under Arthroscopy: A Surgical Technique and Three Cases Report - Song Zhou; Min Cai; Ke Huang (Orthopaedic Surgery, 2020)
Osteochondral fracture of the lateral femoral condyle is a rare intra‐articular injury with or without patellar dislocation. This kind of disease is commonly seen in the knee joint sprain during strenuous activity. At present, open reduction is often used to treat osteochondral fractures. In recent years, with the development of arthroscopy, we have been able to complete the reduction and internal fixation of fractures under arthroscopy. In this paper, three cases of osteochondral fracture of lateral femoral condyle were treated with arthroscopic TWINFIX Ti suture anchor internal fixation, and good results were obtained. After operation, the fracture of femoral condyle healed well and the function of knee joint recovered gradually. Suture anchor system is mostly used to repair rotator cuff and patellar tendon. This is the first case to apply the suture anchor system to the reduction and fixation of fracture.